2013
DOI: 10.1525/auk.2013.13010
|View full text |Cite
|
Sign up to set email alerts
|

Migration timing and wintering areas of three species of flycatchers (Tyrannus) breeding in the Great Plains of North America

Abstract: Abstract.-Descriptions of intra-and interspecific variation in migratory patterns of closely related species are rare yet valuable because they can help assess how differences in ecology and life-history strategies drive the evolution of migration. We report data on timing and location of migration routes and wintering areas, and on migratory speed and phenology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 54 publications
(51 reference statements)
4
48
0
Order By: Relevance
“…b; Jahn et al . ; Lemke et al . ), and late arriving individuals often have lower reproductive success (Kokko ; Smith & Moore ).…”
Section: Discussionmentioning
confidence: 99%
“…b; Jahn et al . ; Lemke et al . ), and late arriving individuals often have lower reproductive success (Kokko ; Smith & Moore ).…”
Section: Discussionmentioning
confidence: 99%
“…Although staging activity is typically attributed to shorebirds and waterfowl (Dunne et al 1982, Newton 2008, numerous geolocator studies have recently reported passerines making stops ranging from 8 to 36 days (Heckscher et al 2011,Åkesson et al 2012, Delmore et al 2012, Tøttrup et al 2012, Callo et al 2013, Fraser et al 2013, Jahn et al 2013, Kristensen et al 2013, Renfrew et al 2013, Wolfe and Johnson 2015, Van Loon et al 2017 that are analogous in length to staging events. Stops of .7 days surpass the amount of time theoretically expected for migratory refueling under optimality models (Alerstam 1991) and have been classified as ''prolonged stopover''-a behavior distinct from typical songbird stopover (McKinnon et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent geolocator studies have also demonstrated a high degree of individual variation in how migration is organized in terms of route and timing [1215]. For example, hoopoes ( Upupa epops ) from a single breeding population in Switzerland chose widely scattered wintering sites in western and eastern Sahel, respectively [14], and golden-crowned sparrows ( Zonotrichia atricapilla ) wintering on the central coast of California (USA) settled at different localities along the coast of the Gulf of Alaska [16] (see also 17], [18). Moreover, Swainson’s thrushes ( Catharus ustulatus ) from a narrow breeding area in south-western Canada exhibited longitudinally separated migratory routes on their southward migration over the North American continent [19] (see also 20).…”
Section: Introductionmentioning
confidence: 99%